Liquidity Indicators Correlate Positively with Financial Returns at Baghdad Soft Drinks: Indikator Likuiditas Berkorelasi Positif dengan Pengembalian Keuangan di Baghdad Soft Drinks - Shnaishel, Thar Saadoon; Herez, Qassim Mahal (Indonesian Journal of Law and Economics Review, 2025)
General Background: Liquidity management plays a critical role in determining the financial sustainability of firms, especially in emerging economies with volatile macroeconomic conditions. Specific Background: In Iraq's industrial sector, firms like Baghdad Soft Drinks Company face liquidity challenges due to currency fluctuations, imported inputs, and evolving consumer demands. Knowledge Gap: Despite global literature affirming the liquidity-performance nexus, few empirical studies have addressed this relationship in Iraqi industrial firms using modern econometric models. Aims: This study investigates the impact of liquidity indicators—current ratio, quick ratio, and cash ratio—on financial performance, measured by return on assets (ROA), controlling for firm size and financial leverage. Results: Using multiple linear regression on data from 2015–2023, findings show all liquidity indicators significantly and positively affect ROA, while firm size also exerts a strong positive influence; financial leverage was statistically insignificant. The model explains 89% of the variance in ROA. Novelty: The study offers a contextualized analytical model adapted to Iraq’s industrial sector, integrating both agency and resource-based theories. Implications: The results highlight strategic opportunities for firms to enhance profitability by optimizing liquidity structures and scaling operations. This research fills a gap in regional financial literature and provides a replicable methodology for similar economies.Highlight : Liquidity indicators (current, quick, cash ratios) significantly improve financial performance (ROA). Firm size positively affects profitability, while financial leverage showed no significant effect. The model explains 89% of ROA variance—demonstrating liquidity's critical role. Keywords : Liquidity, ROA, Financial Leverage, Quick Ratio, Baghdad Soft Drinks